Scientific evidence of guaco biological activity: literature review (Research, Society and Development, 2019)
Plants with potential biological activity in the organism have important applicability in the present day as soon as the use is present in the culture of which it was adhered by the ancestors. The mikania, better known as guaco is used for several pathological conditions, both for cases related to the respiratory system and anti-inflammatory functions in various organs. This work aims to review the literature on the pharmacological effects of Mikania and to know the most used species. In studies done, it was verified that Mikania have several pharmacological effects, with antibacterial in dental infections, anti-hemorrhagic in cases of snakebite, anti-nociceptive with opioid-like actions, anti-inflammatory and antipyretic, useful in cases such as dengue. And this is due to its chemical constitution, since it holds a concentration of important active substances, especially coumarins. It is evident that secondary metabolites have biological activities in the body, with desired effects. M. glomerata was the most searched with positive results against tests. More effort is needed in the evaluation of compounds that can be used by society in the form of drugs with minimal side effects.